The only witness - Scott, Laura, 1961- (Scott, Laura, 1961- Callahan confidential., 2017)
Determined to question the ex-wife of a murder suspect, homicide detective Miles Callahan arrives just in time to save her and her daughter from a shooter. Leaving the scene of a crime goes against his training, but protecting Paige Olson and the little girl is more important than following the rules. But now, on the run with mother and child, Miles must figure out what happened to Paige's ex-husband...and why young Abby won't say a word. Her usually talkative child's silence has Paige worried. Is it possible she witnessed something while video chatting with her dad? If only they can convince the little girl to talk, then they might just break the case wide-open...and stop the killer who's stalking them at every turn.